Improving Student Learning Motivation in Islamic Education Learning with the Cooperative Learning Model: A Study at SD Negeri 8 Tanjung Bonai Aur - Eldayanti (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning motivation in Islamic religious education learning by using a cooperative learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the cooperative learning model can improve student learning motivation in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 42.11%, the first cycle 69.39% and in the second cycle it increased to 89.07%. Thus, the use of the cooperative learning model can be used as an alternative to improve student learning motivation in Islamic religious education learning.